Joining technology and biology to solve conservation problems through translocation in the endangered limpet Patella ferruginea - Espinosa, Free; Maestre, Manuel; García-Gómez, José Carlos; Cotaina-Castro, María Isabel; Pitarch-Moreno, Carmen; Paramio, Juan Manuel; Fort-Santa María, Patricia; García-Estévez, Natalia (Frontiers in Marine Science, 2023)
The current Anthropocene era is characterized by a biodiversity crisis, where many species are pushing to extinction causing alteration of the ecosystems’ stability and loss of their services. In this context, translocation of endangered species could be a powerful resource in conservation as long as its goals and appropriateness are supported enough and matches unambiguous criteria. Patella ferruginea is one of the most endangered marine species in the Mediterranean and several translocations’ efforts have been made with limited results in terms of survival. A methodology that mimics the natural topography of the substrata in the donor population based on Artificial Inert Mobile Substrates (AIMS) is proposed for reinforcing purposes with measures of 40x20x10 cms. Three different treatments were tested: on substrate, slope, and cantilever depending on the position in which the AIMS were deployed. A total of 660 AIMS were installed within the donor area. The installation of such AIMS did not negatively affect neither donor nor receiving populations. A total of 188 specimens were translocated within three different attempts in 2018, 2019 and 2020, and no mortality was observed during the translocation process that lasted 24 h. Survival through the medium and long-term for the translocated specimens ranged from 80.6 to 91.5% after one month, 55.5 to 80.9% after eight months and 48.4 to 76.6% after one year, being the survival in the control population 91.6% after four months and 87.5% after one year. Overall, recruits showed higher survival values than adults and on substrate treatment hosted more specimens (both recruits and adults) than slope and cantilever, but recruits were more abundant on cantilever one. The methodology has been proved to be useful for rutinary reinforcement or reintroduction purposes between donor and receiving areas that could be applied to other sessile or sedentary endangered species.